2020
DOI: 10.3389/fonc.2020.00496
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneities of Site-Specific N-Glycosylation in HCC Tumors With Low and High AFP Concentrations

Abstract: Hepatocellular carcinoma (HCC) is still one of the malignant tumors with high morbidity and mortality in China and worldwide. Although alpha-fetoprotein (AFP) as well as core fucosylated AFP-L3 have been widely used as important biomarkers for HCC diagnosis and evaluation, the AFP level shows a huge variation among HCC patient populations. In addition, the AFP level has also been proved to be associated with pathological grade, progression, and survival of HCC patients. Understanding the intrinsic heterogeneit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 44 publications
1
44
0
Order By: Relevance
“…While the pre-2016 glycoproteomics studies were found to be rather qualitative in their approaches by simply reporting lists of identified glycopeptides as reviewed [ 22 ], our survey of the post-2018 glycoproteomics papers shows that glycopeptide quantification is now commonly applied. Approaches include label-free quantification by XIC or spectral counting [ 50 , 65 ], isotopic dimethyl [ 54 ] or diethyl [ 55 ] labelling as well as TMT [ 52 , 64 ] and DiLeu [ 39 ] labelling, which collectively enable different types of glycopeptide quantitation strategies all regularly used in the field. While glycoproteome mapping studies typically quantify the relative abundance of all glycoforms observed at each glycosylation site to establish a stoichiometric site-specific glycoprofile, comparative glycoproteomics studies often compare the relative quantity of individual glycopeptides or the glycoprofile at each site between conditions.…”
Section: Recent N - and O -Glycmentioning
confidence: 99%
“…While the pre-2016 glycoproteomics studies were found to be rather qualitative in their approaches by simply reporting lists of identified glycopeptides as reviewed [ 22 ], our survey of the post-2018 glycoproteomics papers shows that glycopeptide quantification is now commonly applied. Approaches include label-free quantification by XIC or spectral counting [ 50 , 65 ], isotopic dimethyl [ 54 ] or diethyl [ 55 ] labelling as well as TMT [ 52 , 64 ] and DiLeu [ 39 ] labelling, which collectively enable different types of glycopeptide quantitation strategies all regularly used in the field. While glycoproteome mapping studies typically quantify the relative abundance of all glycoforms observed at each glycosylation site to establish a stoichiometric site-specific glycoprofile, comparative glycoproteomics studies often compare the relative quantity of individual glycopeptides or the glycoprofile at each site between conditions.…”
Section: Recent N - and O -Glycmentioning
confidence: 99%
“…Large-scale glycoproteome profiling and quantification of more than 4700 intact N -glycopeptides from 20 HCC and 20 paired paracancer samples enabled distinguishing low and high AFP level HCCs. Several sialylated but not core fucosylated tri-antennary glycans have been found to be uniquely increased in HCC with low AFP level, while many core fucosylated bi-antennary or hybrid glycans as well as bisecting glycans were uniquely increased in high AFP level tumors [ 190 ]. Differential quantitation analysis revealed that five N -glycopeptides at sites N184 and N241 of serum haptoglobin bearing a monofucosylated triantennary glycan were significantly elevated during the progression from non-alcoholic steatohepatitis (NASH) and cirrhosis to HCC.…”
Section: Screening For Novel Hcc Proteomic Biomarker Candidatesmentioning
confidence: 99%
“…Alpha fetoprotein (AFP) is the most commonly used of serum biomarkers for HCC diagnosis, but the sensitivity and specificity are only 41-65% and 80-90%. 8,9 Traditional imaging modalities that have clinical relevance in HCC diagnosis include ultrasound (US), computed tomography (CT) and magnetic resonance (MR) imaging. 10,11 US has been extensively used as the preferred imaging modality for screening HCC, with a sensitivity ranging from 40% to 80% and a specificity from 82% to 100%.…”
Section: Introductionmentioning
confidence: 99%